2013
DOI: 10.1177/0883073813483569
|View full text |Cite
|
Sign up to set email alerts
|

Complex Febrile Seizures

Abstract: Febrile seizures are the most common type of childhood seizures, affecting 2% to 5% of children. A complex febrile seizure is one with focal onset, one that occurs more than once during a febrile illness, or one that lasts more than 10 to 15 minutes. Confusion still exists on the proper evaluation of a child presenting with a complex febrile seizure. There are ongoing research attempts to determine the link between complex febrile seizures and epilepsy. Further clarification and understanding of this disorder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 36 publications
0
24
0
3
Order By: Relevance
“…Performing EEG within 24 hours of presentation can show generalized background slowing, which could make identifying possible epileptiform abnormalities difficult. Generalized slowing on EEG can be present up to 7 days after a child presents with febrile status epilepticus 24 , 55) . The reported incidence of EEG abnormalities in children with FS varies from 2% to 86% 52 , 53 , 54) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Performing EEG within 24 hours of presentation can show generalized background slowing, which could make identifying possible epileptiform abnormalities difficult. Generalized slowing on EEG can be present up to 7 days after a child presents with febrile status epilepticus 24 , 55) . The reported incidence of EEG abnormalities in children with FS varies from 2% to 86% 52 , 53 , 54) .…”
Section: Discussionmentioning
confidence: 99%
“…A pre-existing lesion can increase the propensity for further focally prolonged seizures and thus cause further hippocampal damage 24) . A recent study found MRI abnormalities in 14.8% of children with complex FS, while only 11.4% of 159 children with simple FS had imaging abnormalities; however, this was not statistically significant 58) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…El electroencefalograma se recomienda únicamente en pacientes con una convulsión febril compleja o estatus epiléptico febril y en pacientes con convulsiones febriles recurrentes. También se recomienda realizarlo en niños que tengan algún retraso en su neurodesarrollo (11). En los casos de convulsiones simples, este estudio no tiene ninguna utilidad (4).…”
Section: Diagnósticounclassified